The High Cost of Raising Provincial Tax Revenues Has Gotten Even Higher - Bev Dahlby (The School of Public Policy Publications)
Households and firms’ responses to higher tax rates alter the volume and the allocation of land, labour and capital in the economy, reducing our income and consumption opportunities. These economic losses from raising tax revenues have increased for provincial governments across Canada in the last decade with the problem being especially acute in Newfoundland and Labrador, Ontario and British Columbia. However, by lowering personal and corporate income tax rates and shifting more of the tax burden to a sales tax harmonized with the federal GST, the provinces could lower the economic cost of raising tax revenues.